2019
DOI: 10.5056/jnm18202
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopic Characterization of Colonic Dysmotility Associated to Opioid and Cannabinoid Agonists in Conscious Rats

Abstract: Background/Aims Gastrointestinal adverse effects have a major impact on health and quality of life in analgesics users. Non-invasive methods to study gastrointestinal motility are of high interest. Fluoroscopy has been previously used to study gastrointestinal motility in small experimental animals, but they were generally anesthetized and anesthesia itself may alter motility. In this study, our aim is to determine, in conscious rats, the effect of increasing doses of 2 opioid (morphine and loperamide) and 1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Possibly, small differences could be better observed by using metabolic cages (although this would introduce additional stress), or delaying the moment of stress application and visualization of the effects through X-rays or, even better, fluoroscopy. 38 When the stressors were applied for 4 consecutive days, we found that the density of content in the stomach remained higher than in the control group; thus, we did not see a clear habituation to the stressful stimuli. The effect of repeated stressful stimuli on stomach emptying is somewhat contradictory in the literature; that is, psychological stress induced by the communicating box decreased gastric emptying when applied chronically, 39 gastric emptying was accelerated when rats were kept in cages filled with 2 cm of water for 5 consecutive days, 40 and habituation to partial restraint stress was found after 5 days of this same stressful stimulus, 2,41 adaptation was not seen after 5 consecutive days of CRF administration.…”
Section: Discussionmentioning
confidence: 57%
“…Possibly, small differences could be better observed by using metabolic cages (although this would introduce additional stress), or delaying the moment of stress application and visualization of the effects through X-rays or, even better, fluoroscopy. 38 When the stressors were applied for 4 consecutive days, we found that the density of content in the stomach remained higher than in the control group; thus, we did not see a clear habituation to the stressful stimuli. The effect of repeated stressful stimuli on stomach emptying is somewhat contradictory in the literature; that is, psychological stress induced by the communicating box decreased gastric emptying when applied chronically, 39 gastric emptying was accelerated when rats were kept in cages filled with 2 cm of water for 5 consecutive days, 40 and habituation to partial restraint stress was found after 5 days of this same stressful stimulus, 2,41 adaptation was not seen after 5 consecutive days of CRF administration.…”
Section: Discussionmentioning
confidence: 57%
“…The ECS is also involved in the control of GI peristalsis and transit [ 14 ]. In particular, CB1 receptors were pointed out as involved in the inhibitory effect of cannabinoids, both, under control [ 167 , 168 , 169 , 170 , 171 ] and under inflammatory conditions [ 172 ]. IBS, or chemotherapy-induced dysmotility are associated with alterations in CB1 and CB2 receptors expression/activity, levels of ECBs or ECB biosynthesis/degradation.…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%